Frequency Regulation Incentive Mechanism and Control Strategy for Electric Vehicles Under Elastic Charging Demand - Xiaohan LI; Wei CAO (Zhongguo dianli)
The high proportion of new energy penetration in the power system poses a serious challenge to frequency stability. With the development of vehicle to grid, electric vehicles as a flexible energy storage system can provide stable frequency regulation services for the power system. In order to enable electric vehicles to provide greater frequency regulation capacity for the power grid and increase users' willingness to participate in frequency regulation, the behavioral characteristics, state of charge, and power constraints of electric vehicles were analyzed. The travel chain and transportation network of electric vehicles were modeled, and a method for optimizing the expected SOC state constraint of electric vehicles was proposed, and the elastic frequency regulation capacity space, incentive mechanism, and frequency regulation control strategy of electric vehicles were constructed. Simulation has verified that compared with traditional control strategies that do not consider elastic charging demand, the proposed control strategy that considers elastic charging demand has advantages in providing frequency regulation capacity for the power grid and increasing user frequency regulation revenue. The proposed control strategy can provide a larger frequency regulation capacity for the power grid, increase users' frequency regulation revenue, and maintain the stability of the power grid frequency.